Elastic-plastic defect interaction in (a)symmetrical double edge notched tension specimens - Kaveh Samadian (AIMS Materials Science, 2017)
Interaction of defects tends to intensify their crack driving force response compared to the situation where these defects act independently. The interaction between multiple defects is addressed in engineering critical assessment standards like BS7910 and ASME B&PV Section XI. Nonetheless, the accuracy of these rules is open to debate since all of them are based on re-characterization procedures which in essence introduce conservativeness. The authors have developed a fully parametric finite element (FE) model able to generate multiple notches in different topologies, in order to investigate their interaction effect. An experimental validation study is conducted to verify the FE model in terms of CTOD response and surface strain distribution. To that end, symmetrically and asymmetrically double edge notched tension specimens are tensile tested and their deformation monitored by means of 3D digital image correlation. In this study the CTOD is opted as a local criterion to evaluate the interaction between notches. These results are compared with an evaluation of strain patterns on a specimen’s surface, as a global interaction evaluation. Through this comparison a deeper understanding is gained to allow us to develop a novel approach to address flaw interaction. Moreover, the validation of the FE model allows future studies of interaction between other defect types (e.g., semi-elliptical, surface breaking) in plate-like geometries.